“Inclusión de niveles de cascarilla de cacao (theobroma cacao l.) en producción de cerdos mixtos en la etapa de acabado en el recinto Todo Santo del cantón El Empalme” - Baque Rosado, Jeison Geonanny (2021)
This research work was developed in the Todo Santo site, which is located on the outskirts of Cantón el Empalme, province of Guayas located west of Pichincha and southwest of Canton Balzar, 166.6 km from the city of Guayaquil. In the present investigation, four levels of cocoa husk inclusion were used. The research source was mixed pigs acquired personally for the investigation since in the enclosure the pig production is low due to the high cost of feeding the pigs, in which they will work with the implementation of a mixture of derivatives prior to physical and chemical analysis and that the present mixture will include four levels of cocoa husk and thus meet the nutritional requirements in mixed pigs The results were: that in the Todo Santo enclosure it only has rice powder feeding which is supplied in small quantities in the morning and in the afternoons food waste is supplied, where the pigs do not have a good adequate diet and does not meet the nutritional requirements necessary for its productive development to carry out this research, sixteen apartments with measures of 1.70 meters long by 80 centimeters wide were built, which were elaborated by rejection of mothers acquired in a sawmill from which A roof, a drinking trough, and feeders were implemented in each department, the floors of which have deep beds, which used rice chaff with a thickness of fifty centimeters, thus avoiding the bad odors of pig feces, we proceeded to the acquisition of the sixteen crossbred pigs for research already acquired, they proceeded to deworm and take its initial weight to develop the research for a period of fifty six, for the present research a completely randomized design (DCA) was applied with four treatments and four repetitions with levels of cocoa husk which were 5%, 10% , 20% and 30% in which we hope to improve the results of meat production with the levels to be used where the best result of meat production reflects us